Academic writing support: A collaboration between the Department of Pharmacy, the Academic Writing Center and the Science Library at the University of Oslo - Lönn-Stensrud, Jessica; Marcellova, Martina; Straume, Ingerid; Soberg, Rigmor; Granås, Anne Gerd (Septentrio Conference Series, 2020)
Higher education across Europe is in transition due to professionalization of the traditional academic education. One response to these changes is to focus on transferable skills (1,2). At the Faculty of Mathematics and Natural Sciences, the vision for the education strategy is that the students shall succeed both scientifically and professionally (3,4). Communication is mentioned as one of the transferable skills important to succeed professionally (4). Clear and comprehensible communication is a crucial transferable skill for pharmacists. Therefore, pharmacy students are evaluated on written communication throughout a 5-year curriculum, including evaluation of e.g. laboratory reports, essays, exams and a master thesis. Over the last decade, the proportion of pharmacy students with Norwegian as native language has decreased. A general impression is also that students in general struggle to express themselves in writing. In 2019, the Department of Pharmacy, the Academic Writing Centre and the Science Library initiated a pilot project aiming to strengthen the academic writing of pharmacy students during the first year of study. 8 seminars about assignment interpretation, text evaluation, and structure and compositions of different assignments, were planned. Further, students were to be mentored in small groups by student mentors. The aim was to provide the pharmacy students with the right tools and skills in writing various academic texts. This presentation will illuminate how University libraries can collaborate with faculties and departments by developing innovative education with the aim for students to gain generic writing knowledge and hands-on skills. We will describe and discuss the series of seminars regarding content, assignments, outcome and progress, from the Science library perspective. The seminars will be evaluated by the students and staff, and the findings will be presented and discussed.